Ancient voices of children [a cycle of songs on texts by George Lorca] for soprano, boy soprano, oboe, mandolin, harp, electric piano [and] percussion - Crumb, George (C.F. Peters, 1970)
A performance of George Crumb's Ancient voices of children, a cycle of songs on texts by Garcia Lorca. Features Jan De Gaetani and the Contemporary Chamber Ensemble conducted by Arthur Weisburg. Combines the music with dance sequences performed by Virginia Johnson.